Rural multimodal planning. Why and how to improve travel options in small towns and rural communities. - Litman, Todd (My University, 2018)
Multimodal planning creates communities where it is possible to get around by walking, cycling and public transportation. This provides various direct and indirect benefits to individuals and communities. This report explores why and how to implement more multimodal planning in rural areas and small towns. Various trends are increasing the importance of multimodal transportation in rural communities including isolation and high transportation costs, aging populations, rising poverty, growing health and safety concerns, and growing tourist industries. Various strategies can help rural communities improve and connect walking, cycling, public transport, including innovative facilities and services, and Smart Growth development policies. New planning resources described in this report can help rural communities and small towns develop integrated multimodal plans and programs.

This report critically evaluates transport policy and project evaluation practices, and describes ways to make them more comprehensive and multi-modal. The conventional transport planning paradigm is mobility-based, it assumes that the planning objective is to maximize travel speed and distance, and evaluates transport system performance based primarily on automobile travel conditions. A new paradigm recognizes that mobility is seldom an end in itself, the ultimate goal of most transport activity is accessibility, which refers to people s overall ability to reach desired services and activities. This new paradigm expands the range of objectives, impacts and options considered in the planning process. It recognizes additional costs from increased motorized transportation and more benefits from walking, cycling and public transport. More comprehensive and multi-modal planning is particularly important in large growing cities where increased motor vehicle traffic imposes particularly large costs, and in developing countries where a major portion of households cannot afford cars.
Keywords: Ländliche Gemeinde; Erreichbarkeit; Verkehrsmittelwahl; Öffentlicher Verkehr; Fahrradverkehr; Fußgängerverkehr; Verkehrsplanung; Verkehrskonzept; Modal Split; Multimodaler Verkehr